2019
DOI: 10.1556/1886.2019.00014
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and immune-modulatory effects of vitamin D provide promising antibiotics-independent approaches to tackle bacterial infections – lessons learnt from a literature survey

Abstract: Antimicrobial multidrug-resistance (MDR) constitutes an emerging threat to global health and makes the effective prevention and treatment of many, particularly severe infections challenging, if not impossible. Many antibiotic classes have lost antimicrobial efficacy against a plethora of infectious agents including bacterial species due to microbial acquisition of distinct resistance genes. Hence, the development of novel anti-infectious intervention strategies including antibiotic-independent approaches is ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 119 publications
(164 reference statements)
3
24
1
Order By: Relevance
“…According to previous in vitro and in vivo investigations, distinct vitamins such as vitamin D and vitamin C exhibited antimicrobial properties [ 34 , 35 ]. Vitamin D, for instance, displayed antibacterial effects against Porphyromonas gingivalis [ 36 ], Streptococcus mutans [ 37 ], and Helicobacter pylori [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous in vitro and in vivo investigations, distinct vitamins such as vitamin D and vitamin C exhibited antimicrobial properties [ 34 , 35 ]. Vitamin D, for instance, displayed antibacterial effects against Porphyromonas gingivalis [ 36 ], Streptococcus mutans [ 37 ], and Helicobacter pylori [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…VitD3 is an important biologically active substance without obvious side effects. In addition to modulating the metabolism of calcium and phosphorus, its antimicrobial and immunomodulatory functions have been demonstrated (Golpour et al, 2019). For example, VitD3 has been reported to be an effective agent to treat tuberculosis by inhibiting mycobacterial lipoarabinomannan and reducing inflammation in the lungs of patients (Liu et al, 2007;Schauber et al, 2007), with similar effects having been shown toward other bacteria, such as E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis and secretion of CAMPs by host cells are significantly enhanced when these cells are exposed to environmental microorganisms and bacteria (Lapis, 2008). As small molecule cationic peptides, CAMPs not only destroy bacteria by directly binding to their cell walls but also inhibit biofilm formation by a variety of bacteria, including P. aeruginosa, Francisella novisida, uropathogenic E. coli, S. aureus, and Aggregatibacter actinomycetemcomitan (Golpour et al, 2019). The results of several studies have demonstrated that the antiinfection role of VitD3 against M. tuberculosis is closely associated with VitD3/VDR-signal mediated antimicrobial responses and the production of CAMP (Liu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a Tb infection, Mtb down-regulates the expression of LL-37 in human macrophages; this reduction can be counteracted by treating the infected macrophages with vitD3, phenylbutyrate (PBA), or their combination [33]. Indeed, 1,25(OH) 2 -vitamin D modulates cathelicidin and defensin gene expression in innate immune cells, such as monocytes and macrophages [34].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%